Barriers to Effective Development and Utilization of Teaching and Learning Materials in Schools (Pashupati Pragya पशुपति प्रज्ञा, 2026)
This paper examines the development and use of teaching and learning materials (TLMs) in Nepalese schools, emphasizing their role in enhancing educational outcomes. It Draw the national performance data and international research, this study identifies inadequate use of instructional materials as a major factor contributing to low student achievement in Nepal. It also highlights the importance of diverse, contextually relevant, and low-cost materials, including locally sourced and ΙCT-integrated resources to promote student engagement, conceptual understanding, and knowledge retention. Despite supportive policies and government budget allocations, TLM integration remains inconsistent due to traditional teacher-entered practices, low levels teacher training, insufficient innovation, and lack of institutional support. This paper provides evidence-based insights into TLM effectiveness and it also offers practical recommendations for teachers, parents, school management committees, and government authorities to support development, accessibility, and classroom implementation. To Strength the use of TLMs is crucial for advancing inclusive, learner centered education and to improve academic performance across Nepal's varied learning contexts.